Report of Government of India - World Bank State Consultation on Indian Marine Fisheries Sector Study : Andhra Pradesh - World Bank (Washington, DC, 2012)
The Department of Animal Husbandry, Dairying and Fisheries, Ministry of Agriculture of Government of India, approached the World Bank to conduct a Study on Indian marine fisheries. Accordingly, a team from the World Bank was undertook the study with special emphasis on marine fisheries in four coastal States viz. Andhra Pradesh, Orissa, Karnataka, and Gujarat. A National Study Report titled 'Indian marine fisheries sector study' was prepared based on the findings of information generated from field visits, secondary data available with various agencies and intensive study of sectoral performance, issues and ways to improve growth of all stakeholders. In a final step taken to ratify and seek consensus regarding the findings and recommendations of the study, state level consultations were held in all four states included in the study, and key issues and analyses placed before state level stakeholder representatives. The consultations were collaborative initiatives of the World Bank, the Department of Animal Husbandry, Dairying and Fisheries, Ministry of Agriculture, Government of India and Action for Food Production (AFPRO), a National NGO identified for the process.